Enhancement of vasculogenesis in mouse embryonic stem cells by alpha 2 macroglobulin activating the LRP1 signaling pathway - Ravindran, Febina; Justus Liebig University Giessen (My University, 2015)
Alpha2m the largest non-immunoglobulin protein present in blood plasma of mammals is an acute phase protein with its serum level elevated upon tissue damage and inflammation. In this study alpha2m administration in mEBs during early differentiation processes resulted in an enhancement of vascularization as assessed with PECAM1 and VE-Cadherin immunofluorescence studies. alpha2m stimulated a dose-dependent increase in protein expression of the endothelial specific markers PECAM1, FLK1 and VE-Cadherin along with up-regulation of the angiogenic growth factors FGF2, VEGF-165 and PDGF-BB. Alpha2m modulates it activity upon binding to and activating its receptors LRP1 and GRP78. Upon blocking with specific antibodies alpha2m mediated vascularization was abolished. Moreover the LRP1 antagonist RAP and inhibitors of the angiogenic growth factors blunted the expression of the growth factors FGF2, VEGF-165 and PDGF-BB along with abolishment of vascularization, suggesting the role of LRP1 receptor in triggering endothelial differentiation signaling. Alpha2m treatment also resulted in the activation of ERK1/2, PI3K, AKT and STAT3 which are all implicated in angiogenic signaling cascades. Their subsequent blocking with their respective inhibitors resulted in the abolishment of vascularization. Investigating the functional characteristic of alpha2m under systematic in-vitro analysis of sprout formation revealed that alpha2m stimulates endothelial cell proliferation and migration inducing vessel formation with longer and branched sprouts.Induction of inflammation in mEBs upon treatment with the inflammatory cytokine TNFa stimulated upregulation of alpha2m and its receptor LRP1 along with increase in vascularization. The vascularization induced by TNFa was abolished upon antibody blocking of the receptor LRP1 suggesting its activation in triggering increased vascularization. In contrast alpha2m treatment resulted in a dose-dependent decrease in the expression of intrinsic TNFalpha along with increase in vascularization, suggesting alpha2m mediates TNFalpha removal by activating LRP1 signaling which could also be responsible for enhanced vascularization in mEBs.In summary this study reports that alpha2m stimulates vasculogenesis in mESCs with upregulation of growth factors and activation of angiogenic signaling pathways. Additionally alpha2m exerts anti-inflammatory effects in mESCs through inhibition of TNFalpha expression.

Alpha2M, das größte nicht-immunglobuläre Protein im Blutplasma von Säugetieren, ist ein Akutphase Protein, dessen Serumwerte im Zuge von Gewebsverletzungen und Entzündungen ansteigen. In dieser Studie konnte gezeigt werden, dass die Gabe von alpha2M in der frühen Phase der Differenzierung von mEBs eine verstärkte Vaskularisierung zur Folge hatte, was durch Immunfluoreszenz-Untersuchungen für PECAM1 und VE-Cadherin nachgewiesen werden konnte. Dabei ist die Stimulierung der Expression der endothelspezifischen Marker PECAM1, FLK1 und VE-Cadherin sowie die Expression der pro-angiogenen Wachstumsfaktoren FGF2, VEGF165 und PDGF-BB durch alpha2M dosisabhängig. Mittels Aktivierung und Bindung seiner Rezeptoren LRP1 und GRP78 wird die Aktivität von alpha2M moduliert. Dabei hat die Blockade der Rezeptoren durch spezifische Antikörper zur Folge, dass der zuvor beobachtete Effekt der Vaskularisierung aufgehoben wird. Eine Behandlung mit dem LRP Antagonisten RAP und Inhibitoren der pro-angiogenen Wachstumsfaktoren zeigte, dass die Expression von FGF2, VEGF165 und PDGF-BB verringert und die Vaskularisierung aufgehoben werden konnte. Dies lässt den Schluss zu, dass der Rezeptor LRP1 eine steuernde Wirkung im Verlauf der Signalübertragung für die endotheliale Differenzierung besitzt. Außerdem zeigte die Behandlung mit alpha2M eine Aktivierung der an der angiogenen Signalkaskade beteiligten Proteine ERK1/2, PI3K, AKT und STAT3. Eine Blockade dieser Proteine mit den jeweiligen Inhibitoren hatte ebenfalls zur Folge, dass der beobachtete Effekt der Vaskularisierung aufgehoben werden konnte. Eine in-vitro Untersuchung des funktionellen Charakters von alpha2M durch einen sprout-formation assay zeigte, dass alpha2M die Proliferation und Migration endothelialer Zellen stimuliert und so die Bildung von langen und verzweigen Gefäßen fördert.Eine durch die Behandlung mit TNFalpha induzierte Entzündungsreaktion in den mEBs hatte eine Stimulierung der alpha2M Bildung und einen Anstieg der LRP1 Expression sowie eine Zunahme der Vaskularisierung zur Folge. Die TNFalpha induzierte Vaskularisierung konnte durch eine Antikörper vermittelte Blockierung des LRP1 Rezeptors aufgehoben werden . Dagegen zeigten sich durch die Behandlung mit alpha2M eine Verringerung der Expression von intrinsischem TNFalpha sowie Dosis-abhängig ein Anstieg der Vaskularisierung. Dies lässt vermuten, dass alpha2M die Herunterregulation von TNFalpha durch die Aktivierung des LRP1 Rezeptors vermittelt, was auch für die verstärkte Vaskularisierung der mEBs verantwortlich sein könnte.Zusammenfassend konnte in dieser Arbeit gezeigt werden, dass alpha2M die Vaskularisierung in mESCs durch eine verstärkte Expression von Wachstumsfaktoren und die Aktivierung von pro-angiogenen Signalwegen stimuliert. Zudem zeigt alpha2M durch die Inhibierung der TNFalpha Expression einen anti-inflammatorischen Effekt in mESCs.
Stimulation der Vaskulogenese embryonaler Stammzellen der Maus durch alpha 2 Makroglobulin und Aktivierung des LRP1 Signalwegs
Keywords: ddc:610